Capsaicin improves glucose homeostasis by enhancing glucagon‐like peptide‐1 secretion through the regulation of bile acid metabolism via the remodeling of the gut microbiota in male mice. Issue 6 (2nd May 2020) - Hui, Suocheng; Huang, Li; Wang, Xiaolan; Zhu, Xiaohui; Zhou, Min; Chen, Mengting; Yi, Long; Mi, Mantian
Abstract: Mounting evidence has linked dietary capsaicin (CAP) consumption to the improvement of glucose homeostasis; however, the underlying mechanisms still need to be further elucidated. Male mice were fed a high‐fat diet (HFD) with CAP administration for 8 weeks, gut microbiota, bile acid (BA) profiles and markers for BA, and glucose metabolism were investigated. CAP improved glucose homeostasis partially by enhancing the secretion of glucagon‐like peptide 1 (GLP‐1). The gut microbiota was remodeled by CAP and was characterized by the increased abundance of Bacteroides genera, which is related with lithocholic acid (LCA) production. LCA is an endogenous agonist of Takeda G‐protein coupled receptor 5 (TGR5); it may enhance GLP‐1 secretion in intestinal L cells. Meanwhile, antibiotics experiment abolished the effects of CAP on glucose homeostasis and microbiota transplantation experiments demonstrated that the CAP‐induced beneficial effects were transferable, indicating that the effects of CAP on glucose homeostasis were largely dependent on the gut microbiota. Additionally, we further identified that the improvements induced by CAP were attenuated by the antagonist of GLP‐1 receptor, indicating that the activation of GLP‐1 signaling contributes to the CAP‐induced improvement in glucose homeostasis.